Heritage dissemination on the web: analysis tool for cultural institutions - Díaz Pérez, Fernando; Martínez Solís, Lorena; Chaín Navarro, Celia (Revista General de Información y Documentación, 2019)
Taking into account the advantages of ubiquity and availability that a website can provide to a museum, it is surprising the low percentage of museums that have one or that when they exist, their websites are more like a simple booklet than an information virtual resource of the 21st century. We have noted the lack of information and training that exists when webmasters develop web pages of museum heritage institutions. Therefore, this work has a double objective, on the one hand to provide directors and managers with an updated guide on what information should be included in the institutional website of a museum, and, on the other hand, to offer an integrated analysis tool that will serve as a zero document to be able to continue working on it in subsequent revisions. This proposal systematizes both previous studies and new parameters and indicators, and is the result of its implementation in more than 100 naval and maritime museums.